2005
DOI: 10.1002/prot.20593
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of predominantly transient protein–protein interfaces

Abstract: A non-redundant set of 170 protein-protein interfaces of known structure was statistically analyzed for residue and secondary-structure compositions, pairing preferences and side-chain-backbone interaction frequencies. By focussing mainly on transient protein-protein interfaces, the results underline previous findings for protein-protein interfaces but also show some new interesting aspects of transient interfaces. The residue compositions at interfaces found in this study correlate well with the results of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 45 publications
12
68
2
1
Order By: Relevance
“…it may vary depending on the external conditions. Protein-protein complexes, which may dissociate or associate depending on the biochemical environment, play an important role in many biological processes, such as signal transduction (Gomperts et al, 2002), electron transport (Brown et al, 1999;Doyle et al, 1986;Ren et al, 1993), transcriptional regulation (Huang et al, 1997;Sengchanthalangsy et al, 1999), growth factors (Lu et al, 1995;Hsu et al, 1997;Bianchet et al, 2000;Blundell et al, 2000), molecular switches (Darling et al, 2000;Pan & Heitman, 2002;Ma & Karplus, 1997), cell-cell recognition (Alattia et al, 1997) and many others (Waas & Dalby, 2002;Cho et al, 2006;Johannes, 2007;Bonet et al, 2006;Ansari & Helms, 2005;Nooren & Thornton, 2003;Schnarr & Khosla, 2006;Vaynberg & Qin, 2006;Fuentes et al, 2006Fuentes et al, , 2007Boelens et al, 1991;Ceres & Zlotnick, 2002;Buts et al, 2001;Nyfeler et al, 2005;Hamelryck et al, 2000). The dissociation constant K d of weak complexes may reach a few hundred mM (Nooren & Thornton, 2003), which corresponds to a ÁG diss of only a few kcal mol…”
Section: General Backgroundmentioning
confidence: 99%
“…it may vary depending on the external conditions. Protein-protein complexes, which may dissociate or associate depending on the biochemical environment, play an important role in many biological processes, such as signal transduction (Gomperts et al, 2002), electron transport (Brown et al, 1999;Doyle et al, 1986;Ren et al, 1993), transcriptional regulation (Huang et al, 1997;Sengchanthalangsy et al, 1999), growth factors (Lu et al, 1995;Hsu et al, 1997;Bianchet et al, 2000;Blundell et al, 2000), molecular switches (Darling et al, 2000;Pan & Heitman, 2002;Ma & Karplus, 1997), cell-cell recognition (Alattia et al, 1997) and many others (Waas & Dalby, 2002;Cho et al, 2006;Johannes, 2007;Bonet et al, 2006;Ansari & Helms, 2005;Nooren & Thornton, 2003;Schnarr & Khosla, 2006;Vaynberg & Qin, 2006;Fuentes et al, 2006Fuentes et al, , 2007Boelens et al, 1991;Ceres & Zlotnick, 2002;Buts et al, 2001;Nyfeler et al, 2005;Hamelryck et al, 2000). The dissociation constant K d of weak complexes may reach a few hundred mM (Nooren & Thornton, 2003), which corresponds to a ÁG diss of only a few kcal mol…”
Section: General Backgroundmentioning
confidence: 99%
“…6 Hydrophobic residues also cluster at some interfaces, [8][9][10] especially large interfaces of obligate or permanent complexes, 5,9,11 whilst other smaller, transient interfaces are less hydrophobic and have a significant number of polar residues. 5,[11][12][13] Hydrophobic residues tend to be scattered over these interfaces in order to accommodate electrostatic interactions, 12 hydrogen bonding and salt bridges. 11,14 Charged side-chains are often excluded from protein-protein interfaces with the exception of arginine.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, secondary structure composition appears to be of little discriminatory value, since neither α-helices nor β-sheets dominate at transient binding sites. 13 Alanine-scanning has shown that binding free energy is not equally distributed at a protein-protein interface 19,20 with the majority of the binding affinity provided by a small number of conserved, polar "hot-spot" residues 21,22 often at the centre of the binding site. 23 Evolutionary conservation has some discriminatory power for obligate and more permanent interactions, 24,25 although protein-protein interfaces in general are often not conserved to the extent where they can be distinguished from other surface patches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have pointed out that dewetting is rare [7][8][9][10] because a few polar residues can prevent the occurrence of dewetting 8,9 . Taking into account the fact that on average ~70% of the interfacial residues of protein complexes are hydrophilic, including ~37% charged residues 11 , hydrophilic interfaces are clearly of larger importance for assembly. The association of hydrophilic surfaces is traditionally thought to result from the direct electrostatic interactions between the binding partners.…”
mentioning
confidence: 99%